A Literata Translator from Russian into Italian: Enrichetta Capecelatro Carafa, Duchess of Andria - Marcucci, Giulia (Translation Studies: Theory and Practice, 2024)
In this paper, I focus on the writer and translator Enrichetta Capecelatro Carafa (1863-1941), who signed all her translations from Russian into Italian, from the 1920s until her death, with the pseudonym Duchess of Andria. Reconstructing the trajectory of this prolific and talented translator means shedding light on one of the many profiles of women translators who worked hard in the early decades of the 20th century to introduce foreign literature into Italy. The case of the Duchess of Andria is emblematic, and at the same time original, for how she approached literary translation, for the number of translations she signed, and for the valuable legacy, still partly unexplored, that she left in the field of translations from Russian. The aim of this work is therefore to document a significant case study, with a brief foray into the field of translation criticism of Chekhov's short stories, translated and prefaced by the Duchess and published in 1936 by Utet.
Keywords: Duchess of Andria; Anton Chekhov; history of translation; women translators